A Comparability of Information in the Financial Statements of Gaming Companies - Małgorzata Czerny; Zuzanna Firkowska-Jakobsze; Stanisław Hońko (Nauki o Finansach)
The purpose of this article is to assess a comparability in the financial statements of entities from the Polish gaming industry. The article uses an unconventional approach to the analysis of comparability of financial statements, with particular emphasis on the business model of the entity. The overall conclusion is that Polish companies used similar accounting policies during the period under review regarding the methods of valuation of assets and liabilities. The scope of disclosures regarding impairment of assets does not allow for a full assessment of the premises underlying them. It is difficult to find out the criteria for qualifying costs for research and development, which are an important asset item. Deficiencies in disclosures are a common feature of the analyzed reports, which can be interpreted as a symptom of their comparability. The analyzed reports, despite the differences diagnosed, make possible to compare the financial situation and achievements of gaming companies.(original abstract)